Modulation of Interleukin‐23 Signaling With Guselkumab in Biologic‐Naive Patients Versus Tumor Necrosis Factor Inhibitor–Inadequate Responders With Active Psoriatic Arthritis - Siebert, S; Coates, LC; Schett, G; Raychaudhuri, SP; Chen, W; Gao, S; Seridi, L; Chakravarty, SD; Shawi, M; Lavie, F; Sharaf, M; Zimmermann, M; et al. (Wiley, 2024)
Objective: We assessed and compared immunologic differences and associations with clinical response to guselkumab, a fully human interleukin (IL)–23p19 subunit inhibitor, in participants with active psoriatic arthritis (PsA) who were biologic‐naive or had inadequate response to tumor necrosis factor inhibitors (TNFi‐IR). Methods: Serum biomarker levels at baseline and after treatment with guselkumab 100 mg every 8 weeks were compared between biologic‐naive (n = 251) and TNFi‐IR (n = 93) subgroups identified in the pooled DISCOVER‐1/DISCOVER‐2/COSMOS data set. Baseline biomarker levels determined by achievement of week 24 clinical responses (≥75%/90% improvement in Psoriasis Area and Severity Index [PASI 75/90], Investigator's Global Assessment [IGA] of psoriasis score 0/1 and ≥2‐point improvement], ≥20% improvement in American College of Rheumatology criteria [ACR20]) were compared between prior treatment subgroups. Results: Baseline IL‐22, TNFα, and beta defensin‐2 (BD‐2) levels were significantly lower in biologic‐naive than in TNFi‐IR participants. With guselkumab, week 24 IL‐17A, IL‐17F, IL‐22, serum amyloid A, C‐reactive protein, IL‐6, and BD‐2 levels were significantly reduced from baseline in biologic‐naive and TNFi‐IR participants (≥1.4‐fold difference, nominal P < 0.05). Clinical responders to guselkumab exhibited significantly higher baseline levels of several biomarkers than nonresponders (IL‐17A, IL‐17F, BD‐2 in biologic‐naive PASI 90 responders; IL‐17A, BD‐2 in TNFi‐IR IGA 0/1 responders; IL‐22, BD‐2 in TNFi‐IR PASI 90 responders [nominal P < 0.05]) and trended higher in TNFi‐IR ACR20 responders. Conclusion: Guselkumab modulates IL‐23 signaling and provides consistent pharmacodynamic effects in both biologic‐naive and TNFi‐IR PsA patients. Significantly elevated baseline IL‐22, TNFα, and BD‐2 levels and associations between baseline IL‐22, IL‐17A, and BD‐2 levels and skin responses to guselkumab suggest greater dysregulation of IL‐23/Th17 signaling in patients with TNFi‐IR.